A graphite material and its preparation method and application

By mechanical grinding and pretreatment of focusing material, the deterioration of graphite negative electrode materials in high-temperature storage and cycling performance is solved, the process is simplified and the cost is reduced, and high-performance graphite material preparation is achieved to meet the high level of lithium battery negative electrode materials. Performance requirements.

CN116354342BActive Publication Date: 2025-01-17HUNAN SHINZOOM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111621394.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-01-17
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

The existing graphite anode materials have deteriorated in high-temperature storage and cycling performance, and the preparation process is complex and costly, making it difficult to meet the high-performance needs of lithium battery anode materials.

Method used

Use combust materials with isotropicity within a certain range of conditions for mechanical grinding and pretreatment to remove components with low hardness, improve Hastello abrasiveness index, simplify the preparation process and directly obtain single-particle graphitized materials to avoid granulation process, reduce costs.

Benefits of technology

The high-temperature storage and cycling performance of graphite chemicals is improved, so that graphite materials can be used as a long-life energy storage negative electrode material, simplifying the process and saving costs, and the capacity retention rate after 1,000 cycles can reach more than 94.2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116354342B_ABST
    Figure CN116354342B_ABST
Patent Text Reader

Abstract

The present invention provides a graphite material and a preparation method and application thereof. The preparation method comprises: subjecting a coke-like material to mechanical grinding pretreatment, shaping and graphitization treatment to obtain the graphite material; wherein the isotropy of the coke-like material satisfies: in the coke-like material, the sum of the long and thin fiber structure and the wide-area structure is ≤10%, the sum of the medium and short fiber structure and the coarse mosaic structure is ≥70%, and the fine mosaic structure is ≤20%. The present invention selects coke-like materials with isotropy within a certain range of conditions as raw materials, and simultaneously subjecting them to mechanical grinding pretreatment, so as to effectively remove components with low hardness in the raw materials, improve the Hastelloy grindability index of the raw materials, improve the stability of the subsequent entire powder making process, and reduce the amount of fine powder generated during the powder making process, thereby improving the high-temperature storage and cycle performance of the graphitized product, so that the final graphite material can be used as a long-life energy storage negative electrode material, while simplifying the process and saving costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite negative electrode material preparation, and relates to a graphite material and a preparation method and application thereof. Background Art

[0002] Graphite is often used in the preparation process of negative electrode materials for lithium batteries because of its good electrical conductivity. It has the advantages of high degree of crystallization, high specific capacity and good processing performance. With the advancement and development of science and technology, the demand for negative electrode materials for lithium batteries has also increased.

[0003] The basic requirements of the current market for graphite negative electrode energy storage materials are as follows: capacity ≥335mAh / g, compaction ≥1.50g / cc, and cycle number (capacity retention rate 80% cutoff) ≥5000 cycles. The cycle number of graphite negative electrode energy storage materials on the market is generally 5000-6000 cycles.

[0004] CN101916857A discloses a composite negative electrode material for lithium-ion power and energy storage batteries, a preparation method thereof, and a battery. The technical problem to be solved is to improve the high-rate discharge performance of the battery. Composite particles are formed by combining hard carbon and natural graphite, or hard carbon and artificial graphite, or hard carbon and natural graphite and artificial graphite. Preparation method: hard carbon, natural graphite and / or artificial graphite are mixed with a dispersant and water to obtain a mixture, which is then dried and heat-treated. The negative electrode material of the battery of the present invention adopts the material. The material in the document has a large cycle attenuation (300-cycle capacity retention rate is 83%).

[0005] CN106395810A discloses a method for preparing a low-graphitization HEV graphite negative electrode material, comprising the following steps: (1) mixing petroleum coke or asphalt coke with a coating material; (2) subjecting the mixture to thermal polymerization at a temperature of 350 to 500°C, wherein the thermal polymerization reaction pressure is 0.01 to 10 MPa and the reaction time is 50 to 420 minutes; (3) composite granulation; (4) subjecting the granulated material to low-temperature graphitization at 2000 to 2600°C to obtain a carbon negative electrode material with a surface coated with composite artificial graphite. CN106654269A is to mix the carbon material and asphalt powder uniformly, and then use a horizontal granulation kettle to granulate (in a nitrogen atmosphere, the temperature is raised from room temperature to 500 to 1000°C at a heating rate of 2°C / min to 5°C / min, and then the temperature is lowered to room temperature after being kept for 0.5 to 6 hours), and then carry out subsequent processes such as graphitization treatment. CN106276910A is to mix the carbon material with the dispersant, perform granulation by spray drying technology, and then perform subsequent processes such as graphitization. The above three documents generally use the granulation process to perform granulation, and then perform graphitization on the composite particles, but the cost of the composite granulation + graphitization process is relatively high.

[0006] Petroleum coke is a common raw material for preparing graphite. During the production process, some areas with rich mosaic structures will be produced. Since these areas will cause more defects in the raw materials, they will lead to lower hardness, unstable powder making, more fine powder produced by powder making, and lower overall capacity and compaction of graphitized products, as well as deterioration of high-temperature storage and cycle performance.

[0007] Therefore, how to process graphite raw materials, simplify the graphite preparation process, and improve the electrochemical performance of the obtained graphite material when used as a negative electrode is a technical problem that needs to be solved urgently. Summary of the invention

[0008] The purpose of the present invention is to provide a graphite material and a preparation method and application thereof. The present invention selects a coke-like material with isotropy within a certain range of conditions as the raw material for preparing the graphite material, and performs mechanical grinding pretreatment on it, which can effectively remove the components with low hardness in the raw material, improve the Hardgrove Grindability Index (HGI) value of the raw material, improve the stability of the subsequent entire powder making process, and reduce the amount of fine powder generated in the subsequent powder making process, thereby improving the high-temperature storage and cycle performance of the graphitized product, so that the final graphite material can be used as a long-life energy storage negative electrode material, and at the same time simplifies the process, does not require granulation, and further saves costs.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a graphite material, the preparation method comprising:

[0011] The coke-like material is subjected to mechanical grinding pretreatment, shaping and graphitization treatment to obtain the graphite material;

[0012] Among them, the isotropy of the coke-like material satisfies: in the coke-like material, the sum of the long and thin fiber structure and the wide-area structure is ≤10%, for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2% or 1%, etc., the sum of the medium and short fiber structure and the coarse mosaic structure is ≥70%, for example, 70%, 72%, 75%, 78%, 80%, 83%, 85%, 90%, 95% or 99%, etc., and the fine mosaic structure is ≤20%, for example, 20%, 18%, 15%, 13%, 10%, 8%, 5%, 3%, 2% or 1%, etc.

[0013] In the present invention, the isotropy of the coke-like material is a common characterization of the upstream coke raw material production enterprises of the negative electrode. It is distinguished according to the size of the isochromatic area in the polarizing microscope. Long and thin fibers are long fibers, wide areas are large areas, and medium and short fibers are medium fibers and short fibers (standard reference for isotropy: Du Yong, Liu Chunfa, Shan Changchun, et al. Polarized light microscopic analysis method of needle-shaped coke and discussion on influencing factors [J]. Carbon Technology, 2007, 26(6):3).

[0014] The present invention selects a coke-like material with isotropy within a certain range of conditions as the raw material for preparing the graphite material, and performs mechanical grinding pretreatment on the material, thereby effectively removing components with low hardness in the raw material, improving the Hastelloy Grindability Index (HGI) value of the raw material, improving the stability of the subsequent entire powder making process, reducing the amount of fine powder generated in the powder making process, and improving the high-temperature storage and cycle performance of the graphitized product, so that the finally obtained graphite material can be used as a long-life energy storage negative electrode material. At the same time, the process is simplified, and no granulation is required, and a single-particle graphitized material is directly obtained, which further saves costs.

[0015] In the present invention, by mechanically grinding the coke-like material whose isotropy meets the above conditions for pretreatment, the part with more defects, poor strength and enriched fine mosaic structure in the coke-like material is effectively reduced; thereby improving the HGI value of the raw material, the stability of the powder making process, and reducing the amount of fine powder produced during the powder making process.

[0016] In the present invention, if the coke-like material is not pre-treated by mechanical grinding, the defective parts cannot be effectively removed, which will cause fluctuations in the powder making process and smaller D00 and D10 of the material obtained after powder making (ie, too much fine powder).

[0017] Preferably, the mechanical grinding pretreatment method comprises stirring and grinding in a vertical kettle.

[0018] Preferably, no heating is required during the mechanical grinding pretreatment process.

[0019] Preferably, the stirring and grinding time is 1 to 6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0020] In the present invention, if the stirring and grinding time is too short, it is not conducive to the full removal of defective parts, while if the time is too long, it will lead to lower pretreatment capacity, excessive wear of raw materials, a higher proportion of screening removal, and lower pretreatment raw material yield.

[0021] Preferably, the frequency of the stirring and grinding is 10 to 40 Hz, for example, 10 Hz, 13 Hz, 15 Hz, 18 Hz, 20 Hz, 23 Hz, 25 Hz, 28 Hz, 30 Hz, 32 Hz, 35 Hz, 38 Hz or 40 Hz.

[0022] Preferably, the water content of the char-like material is ≤1%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc.

[0023] In the present invention, the water content of the coked material can be reduced by drying the coked material. When the water content is within the range of ≤1%, it is more conducive to the dispersion of the raw materials and thus the complete removal of the defective parts. When the water content is greater than 1%, the materials will agglomerate, the particles will stick together or to the inner wall of the equipment or the blades, and the defective parts will not be able to be fully polished and completely removed.

[0024] Preferably, before the mechanical grinding pretreatment, the charred material is first subjected to a coarse crushing treatment.

[0025] Preferably, the shaping treatment time is 30 to 600 s, for example, 30 s, 50 s, 100 s, 150 s, 200 s, 250 s, 300 s, 350 s, 400 s, 450 s, 500 s, 550 s or 600 s.

[0026] Preferably, before the shaping process, the material after mechanical grinding pretreatment is crushed.

[0027] In the present invention, after mechanical grinding pretreatment, the crushing and shaping are carried out directly without the need for a granulation process, thereby saving the use of adhesives, VC stirring steps and granulation steps, and further saving raw material costs and production costs.

[0028] Preferably, the temperature of the graphitization treatment is 2800-3200°C, for example, 2800°C, 2900°C, 3000°C, 3100°C or 3200°C.

[0029] Preferably, the median particle size of the graphite material is 8 to 20 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0030] As a preferred technical solution, the preparation method comprises:

[0031] The coke-like material is roughly broken, and then stirred and polished in a vertical kettle at a stirring frequency of 10 to 40 Hz for 1 to 6 hours, shaped for 30 to 600 seconds, and graphitized to obtain a graphite material with a median particle size of 8 to 20 μm;

[0032] The isotropy of the coke-like material satisfies the following conditions: in the coke-like material, the sum of long and thin fiber structure and wide-area structure is ≤10%, the sum of medium and short fiber structure and coarse mosaic structure is ≥70%, the fine mosaic structure is ≤20%, and the water content of the coke-like material is ≤1%.

[0033] In a second aspect, the present invention provides a graphite material, wherein the graphite material is prepared by the method for preparing the graphite material as described in the first aspect.

[0034] The graphite material provided by the present invention can be used as a primary negative electrode material and further subjected to operations such as carbon coating.

[0035] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the graphite material as described in the second aspect.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention selects a coke-like material with isotropy within a certain range of conditions as the raw material for preparing graphite material, and performs mechanical grinding pretreatment on it, which can effectively remove the components with low hardness in the raw material, improve the Hardgrove Grindability Index (HGI) value of the raw material, improve the stability of the subsequent entire powder making process, and reduce the amount of fine powder produced by powder making, thereby improving the high-temperature storage and cycle performance of the graphitized product, so that the final graphite material can be used as a long-life energy storage negative electrode material, and at the same time simplifies the process, does not require granulation, and further saves costs. The battery provided by the present invention has a capacity retention rate of more than 90.3% after 1000 cycles at a high temperature of 45°C and 1C, and further controls the stirring time, and the capacity retention rate after 1000 cycles at 1C can reach more than 94.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is an optical structure diagram of the small coke particles provided in Example 1 before mechanical grinding (vertical kettle stirring).

[0039] Figure 2 This is an optical structure diagram of the small coke particles provided in Example 1 after mechanical grinding (vertical kettle stirring).

[0040] Figure 3 This is a SEM picture of the small coke particles provided in Example 1 before mechanical grinding (vertical kettle stirring).

[0041] Figure 4 This is a SEM image of the small coke particles provided in Example 1 after mechanical grinding (vertical kettle stirring). DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing a graphite negative electrode material, and the preparation method is as follows:

[0045] (1) The petroleum coke raw material is crushed by a coarse crusher at a frequency of 40 Hz to obtain small coke particles with a particle size of 5 mm;

[0046] The isotropy of petroleum coke raw materials meets the following requirements: the sum of long and thin fiber structure and wide-area structure is 10%, the sum of medium and short fiber structure and coarse mosaic structure is 70%, and the fine mosaic structure is 20%;

[0047] (2) After drying the coke particles to a moisture content of 0.8%, the particles are placed in a vertical kettle and stirred at a frequency of 40 Hz for 1 h. The ground raw materials are sieved through a 30-mesh sieve to remove fine powder (components with low hardness in the raw materials). The sieved raw materials are crushed and shaped. The shaping time is 300 s. The parameters of the shaping machine are 40 Hz. The shaped materials are graphitized at 3000° C. for 15 h to obtain a graphite material with a median particle size of 15 μm.

[0048] Figure 1 The optical structure of the coke particles provided in Example 1 before mechanical grinding (vertical kettle stirring) is shown. Figure 2 The optical structure diagram of the coke small particles after mechanical grinding (vertical kettle stirring) provided in Example 1 is shown. Figure 1 The left edge of the middle coke is filled with a large number of mosaic-like fine inlay structures, with some holes (in the white line mark area) distributed between these structures. Figure 2 After the raw materials in the coke are mechanically polished, the structure disappears obviously, the coke is dense inside, and the mosaic structure disappears obviously. Figure 1 and Figure 2 It can be seen from the comparison that after mechanical grinding, the edge part with hole defects and enriched fine mosaic structure is fully removed.

[0049] Figure 3 The SEM image of the coke particles provided in Example 1 before mechanical grinding (vertical kettle stirring) is shown. Figure 4 The SEM image of the coke particles provided in Example 1 after mechanical grinding (vertical kettle stirring) is shown. Figure 3 and Figure 4 It can be seen from the comparison that after the coke is ground, the semi-finished powder obtained is less fine powder and the particle size is more uniform.

[0050] Example 2

[0051] This embodiment provides a method for preparing a graphite negative electrode material, and the preparation method is as follows:

[0052] (1) The petroleum coke raw material is crushed by a coarse crusher at a frequency of 40 Hz to obtain small coke particles with a particle size of 2 mm;

[0053] The isotropy of petroleum coke raw materials meets the following requirements: the sum of long and thin fiber structure and wide-area structure is 8%, the sum of medium and short fiber structure and coarse mosaic structure is 80%, and the sum of fine mosaic structure is 12%;

[0054] (2) After drying the coke particles to a moisture content of 1%, the particles are placed in a vertical kettle and stirred at a frequency of 10 Hz for 6 h. The ground raw materials are sieved through a 30-mesh sieve to remove fine powder (components with low hardness in the raw materials). The sieved raw materials are crushed and shaped. The shaping time is 600 s. The parameters of the shaping machine are 40 Hz. The shaped materials are graphitized at 2800° C. for 20 h to obtain a graphite material with a median particle size of 10 μm.

[0055] Example 3

[0056] (1) The petroleum coke raw material is crushed by a coarse crusher at a frequency of 35 Hz to obtain small coke particles with a particle size of 10 mm;

[0057] The isotropy of petroleum coke raw materials meets the following requirements: the sum of long and thin fiber structure and wide-area structure is 5%, the sum of medium and short fiber structure and coarse mosaic structure is 90%, and the sum of fine mosaic structure is 5%;

[0058] (2) After drying the coke particles to a moisture content of 1%, they are placed in a vertical kettle and stirred at a frequency of 25 Hz for 3.5 h. The ground raw materials are sieved through a 30-mesh sieve to remove fine powder (components with low hardness in the raw materials). The sieved raw materials are crushed and shaped. The shaping time is 600 s. The parameters of the shaping machine are 40 Hz. The shaped materials are graphitized at 2800° C. for 30 h to obtain a graphite material with a median particle size of 20 μm.

[0059] Example 4

[0060] The difference between this embodiment and embodiment 1 is that the water content of the small coke particles in step (2) of this embodiment is 2%.

[0061] The rest of the preparation methods and parameters were the same as those in Example 1.

[0062] Example 5

[0063] The difference between this embodiment and embodiment 1 is that the stirring time in the vertical kettle in step (2) of this embodiment is 0.5 h.

[0064] The rest of the preparation methods and parameters were the same as those in Example 1.

[0065] Example 6

[0066] The difference between this embodiment and embodiment 1 is that the stirring time in the vertical kettle in step (2) of this embodiment is 6.5 h.

[0067] The rest of the preparation methods and parameters were the same as those in Example 1.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 1 is that the stirring and grinding in the vertical kettle in step (2) is not performed.

[0070] The rest of the preparation methods and parameters were the same as those in Example 1.

[0071] Comparative Example 2

[0072] This comparative example provides a graphite material, and the preparation method of the graphite material is as follows:

[0073] The petroleum coke raw material was crushed to 10 μm, 10% petroleum asphalt was added, granulated at 400°C for 5 hours in a vertical kettle, and then graphitized (graphitized at 3000°C for 15 hours) and sieved to obtain a product with a particle size specification of 15 μm.

[0074] The graphite materials provided in Examples 1-6 and Comparative Examples 1-2 were mixed with sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and conductive ink black (Super-P) in a mass ratio of 95:2:1.5:1.5 to obtain a slurry (homogenization environment: temperature 25±3°C), and the slurry was evenly applied to a 10μm copper foil, and the surface of the foil should be smooth without damage or wrinkles. After baking, slitting, rolling and sheeting, a negative electrode sheet was prepared. The negative electrode sheet described above was used as the negative electrode, and the lithium cobalt oxide sheet was used as the positive electrode. A 12μm aluminum foil was used for positive electrode coating, and the surface of the foil should be smooth without damage or wrinkles. After winding, top and side sealing, liquid injection, sealing and aging, a lithium battery was prepared, and then a cycle performance test was carried out under high temperature 45°C test conditions, 1C current constant current charging to 4.2V, then constant voltage charging to 0.05C, and then 1C discharge to 3.0V, so that 1000 cycles were repeated. The results are shown in Table 1.

[0075] Table 1

[0076]

[0077]

[0078] It can be seen from the data results of Example 1 and Example 4 that before mechanical polishing, the water content of the raw material is too high, which will result in the cycle performance of the graphitized product being unable to be significantly improved.

[0079] From the data results of Example 1 and Examples 5 and 6, it can be seen that during the mechanical grinding process, if the stirring time is too short, the cycle performance cannot be significantly improved, and if the stirring time is too long, the cycle performance will not be further improved, and the pretreatment yield will be reduced.

[0080] It can be seen from the data results of Example 1 and Comparative Example 1 that it is difficult to improve the battery cycle performance without mechanical polishing pretreatment.

[0081] From the data results of Example 1 and Comparative Example 2, it can be seen that compared with the conventional preparation method of graphite material, the preparation method provided by the present invention does not require granulation, has a simple preparation process, and saves costs. At the same time, the prepared material has high high-temperature cycle performance, and the capacity retention rate is still above 94% after 1000 cycles.

[0082] In summary, the present invention selects coke-like materials with isotropy within a certain range of conditions as raw materials for preparing graphite materials, and pre-treats them by mechanical grinding, which can effectively remove components with low hardness in the raw materials, improve the Hardgrove Grindability Index (HGI) value of the raw materials, improve the stability of the subsequent entire powder making process, reduce the amount of fine powder produced by powder making, and improve the high-temperature storage and cycle performance of graphitized products, so that the final graphite material can be used as a long-life energy storage negative electrode material, and at the same time simplify the process, no granulation is required, and further save costs. The battery provided by the present invention has a capacity retention rate of more than 90.3% after 1000 cycles at a high temperature of 45°C and 1C, and the capacity retention rate after 1000 cycles at 1C can reach more than 94.2% by further adjusting the stirring time.

[0083] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a graphite material, characterized in that: The preparation method comprises: The coke-like material is subjected to mechanical grinding pretreatment, shaping and graphitization treatment to obtain the graphite material; The isotropy of the coke-like material satisfies: in the coke-like material, the sum of the long and thin fiber structure and the wide-area structure is ≤10%, the sum of the medium and short fiber structure and the coarse mosaic structure is ≥70%, and the fine mosaic structure is ≤20%; The mechanical grinding pretreatment method includes stirring and grinding in a vertical kettle, and the mechanical grinding pretreatment process does not require heating; The stirring and grinding time is 1 to 6 hours; The water content of the coke-like material is ≤1%.

2. The method for preparing graphite material according to claim 1, characterized in that: The frequency of the stirring and grinding is 10-40 Hz.

3. The method for preparing the graphite material according to claim 1, characterized in that: Before the mechanical grinding pretreatment, the coke-like material is firstly subjected to a rough crushing treatment.

4. The method for preparing a graphite material according to claim 1, characterized in that: The shaping process takes 30 to 600 seconds.

5. The method for preparing a graphite material according to claim 1, characterized in that: The median particle size of the graphite material is 8-20 μm.

6. The method for preparing graphite material according to claim 1, characterized in that: The preparation method comprises: The coke-like material is roughly broken, and then stirred and polished in a vertical kettle at a stirring frequency of 10-40 Hz for 1-6 hours, shaped for 30-600 seconds, and graphitized to obtain a graphite material with a median particle size of 8-20 μm; Among them, the isotropy of the coke-like material satisfies: in the coke-like material, the sum of long and thin fiber structure and wide-area structure is ≤10%, the sum of medium and short fiber structure and coarse mosaic structure is ≥70%, the fine mosaic structure is ≤20%, and the water content of the coke-like material is ≤1%.

7. A graphite material, characterized in that: The graphite material is prepared by the method for preparing a graphite material according to any one of claims 1 to 6.

8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the graphite material as claimed in claim 7.

Citation Information

Patent Citations

  • Composite cathode material for lithium ion power and energy storage battery and preparation method thereof and battery

    CN101916857A

  • Preparation method of low temperature graphite anode material for lithium ion battery

    CN106276910A

  • Preparation method of graphite negative electrode material used for low graphitization degree HEV

    CN106395810A

  • Graphite negative electrode material used for power lithium ion battery and preparation method and application of graphite negative electrode material

    CN106654269A

  • Electrode material and secondary battery

    CN109461934A